2012
DOI: 10.1118/1.4734845
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐J‐12: Initial Clinical Experiences in Using 4D‐CBCT as Image Guidance for Lung SBRT

Abstract: 4D-CBCT is a superior image guidance technique for lung SBRT treatments for its ability to visualize moving target. It provides physicians more confidence in tumor targeting and ability to repeatedly evaluate ITV quality during the treatment course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Symmetry automatically sorts images into ten phases based on automatic detection of diaphragm position. 31 ) do not necessarily result in higher dose compared with other protocols, which are 3D protocols. Table V also indicated that for the XVI imaging protocols, the measured doses were in good agreement with the nominal doses provided by the Vendor.…”
Section: Discussionmentioning
confidence: 93%
“…Symmetry automatically sorts images into ten phases based on automatic detection of diaphragm position. 31 ) do not necessarily result in higher dose compared with other protocols, which are 3D protocols. Table V also indicated that for the XVI imaging protocols, the measured doses were in good agreement with the nominal doses provided by the Vendor.…”
Section: Discussionmentioning
confidence: 93%
“…[301][302][303][304][305] Despite the aforementioned challenges, researchers have done a tremendous amount of work to address these issues, and 4D-CBCT has been shown to be of important clinical utility. Multiple studies have reported superior target visualization and increased confidence in ITV localization with 4D-CBCT technology, thereby recommending it as a more accurate image-guidance technique for moving targets as compared to 3D-CBCT, [306][307][308][309][310][311] even improving the interobserver variability. 312 Four dimensional CBCT was shown to result in dosimetric advantages via the ability to reduce margins and thus irradiate less normal tissue, 313 as well as facilitating accurate verification of target position for both inter-and intra-fractional motion for lung SBRT with VMAT delivery.…”
Section: B Investigated Solutionsmentioning
confidence: 99%